Slang Words Used by TikTok Users: Types and Functions - Michelle Kezia Wenas; Siti Aisyah Aisyah; Endah Alamsari Andayani (Journal of English Language and Education, 2026)
Slang has become a significant feature of informal communication on social media, particularly on TikTok, where language develops rapidly through viral trends. According to Allan and Burridge (2006), slang is inherently innovative and shaped by social context; however, limited studies have systematically examined the types of slang used by TikTok users and their communicative functions. This study aims to identify the dominant types of slang used by TikTok users and analyze their communicative functions in TikTok interactions. A descriptive qualitative method with content analysis was employed, using 20 slang expressions used by TikTok users collected from videos, captions, and comment sections. The data were selected using purposive sampling, in which slang expressions were chosen based on their relevance to the research objectives and their frequency of use in TikTok interactions. The findings reveal that Fresh and Creative is the most dominant slang type (10 items), while expressing admiration or evaluation is the most frequent communicative function (9 items). These results indicate that slang used by TikTok users functions as a strategic communicative resource that supports social interaction and reflects ongoing linguistic innovation in digital communication.